'Pre-launch' finite element analysis of a short-stem total hip arthroplasty system consisting of two implant types. (January 2019) - Lerch, Matthias; Windhagen, Henning; Kurtz, Agnes-Elisabeth; Budde, Stefan; Behrens, Bernd-Arno; Bouguecha, Anas; Almohallami, Amer
Abstract: Background: We applied a previously established and validated numerical model to a novel short-stemmed implant for a 'pre-launch' investigation. Methods: The implant system consists of two different implant geometries for valgus/varus-positioned proximal femurs with differences in volume distribution, head/neck angle, and calcar alignment. The aim of the design was to achieve a better adaption to the anatomic conditions, resulting in a favourable load transfer. The implant type G showed the best fit to our model, but both stem geometries were implanted; the implant type B was used to compute an 'imperfection scenario'. Findings: Apparent bone density decreased by 4.3% in the entire femur with the implant type G, and by 12.3% with the implant type B. Bone mass loss was pronounced in the proximal calcar region. Apparent bone density increased at the lateral cortical ring and in the minor trochanter. The apparent bone density in the imperfection scenario was very similar to that of a straight stem, indicating a distal load transfer. Interpretation: No adverse effects of the A2 short-stemmed implant system on bone remodeling could be detected. The overall bone density reduction was acceptable, and wedge fixation was not observed, indicating that there was no distal load transfer. The simulation of an incongruous implant indicates the sensitivity of our model in response to modifications of implant positioning. Correct implant selection and positioning is crucial when using the A2 system. Highlights: No adverse effects of the A2 short-stem on bone remodeling could be detected. Bone remodeling is comparable to those of previous investigations. Bone density increased at the lateral cortical ring and in the minor trochanter. The simulation of an incongruous implant leads to a pronounced bone mass reduction.